KARAKTERISASI FTIR DAN UJI TOKSISITAS HIDROKSIAPATIT NANOKRISTALIN Corbicula moltkiana TERHADAP SEL HUMAN DERMAL FIBROBLAS ADULT - Al Majiid, Muhammad Shalahuddin; Pascawinata, Andries; Lestari, Citra (Universitas Baiturrahmah, 2025)
Background: One way to reconstruct bones is with bone grafting. Hydroxyapatite (HA) is often used as a bone graft, because it has biocompatibility, osteoconductive, bioactive, non-toxic and non-immunogenic properties. HA can be obtained from natural materials such as shells, limestone, egg shells and others. Using natural materials has several advantages such as high Ca/P ratio content, abundant quantities, and cheaper material production costs. The nanocrystalline hydroxyapatite (nHA) used in this research is Corbicula moltkiana shell powder. Purpose: to know; a) FTIR characterization of nHA Corbicula moltkiana; b) the level of toxicity of Corbicula moltkiana nHA on HDFA cells, and c) the ideal concentration of Corbicula moltkiana nHA on HDFA cell viability. Methods: in vitro laboratory experiment with post-test only control group design. To find out the characterization, use the FTIR characterization test. Toxicity test using the MTT method. The research samples were Corbicula moltkiana nHA powder and HDFA cells. The samples were divided into 4 groups, namely the control cell group and 3 groups of nHA Corbicula moltkiana with concentrations of 25 µg/ml, 50 µg/ml, and 100 µg/ml. Results: 1) Corbicula moltkiana nHA powder has good HA quality, 2) cell viability at concentrations of 25 µg/ml, 50 µg/ml, and 100 µg/ml against HDFA cells was 99.64%, 96.51% and 83.93%, respectively. Conclusions: 1) the higher the concentration of Corbicula moltkiana nHA, the lower the viability of HDFA cells, but all concentrations studied were not toxic, 2) Corbicula moltkiana nHA is biocompatible with HDFA cells.